POTENSI EKONOMI DAN PENGELOLAAN SAMPAH PASAR DI KOTA BANDAR LAMPUNG - Santosa, Imam; Sujito, Enro (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2020)
Marketâ€™s solid waste that has accumulated can cause air pollution in the form of an odor that disturbs market visitors, traders, and residents around the market. Solid waste that has accumulated is a breeding place for disease vectors, such as flies, cockroaches, and mosquitoes.This research aims to solve the problem of market waste management in the city of Bandar Lampung. Primary data obtained from survey results and direct measurements, namely the volume of waste generation, type of waste, and the composition of waste. Secondary data were obtained from market managers.Market waste management has not used the concept of waste reduction and waste management mandated in the Bandar Lampung City Laws and Regulations, the average amount of waste generation throughout the market is 46,747 kg/day, the average per day of each market ranges from 3,438 -11,703 kg/day. The type and composition of waste is an organic waste of 84.48% and inorganic waste of 15.52%. The economic potential of all market waste is Rp. 12,938,816/day or Rp. 388,164,480/month and Rp. 4,657,973,760/year. It is necessary to plan 3R TPS and socialize waste management following the mandate of Law No. 18 of 2008 concerning Waste Management, as well as the Regional Regulation of the City of Bandar Lampung No. 5 of 2015 concerning Waste Management in the City of Bandar Lampung.Â